EVALUATION AND STUDY OF SOME CHEMICAL AND MICROBIOLOGICAL CHARACTERISTICS OF INDUSTRIAL WATER WASTE FROM THREE OIL COMPANIES (Eureka Journal of Physical and Chemical Research, 2026)
This study included an assessment of the quality of liquid industrial waste from three oil companies: Baiji Refineries Company (A) near Tikrit, the North Oil Company inside the city of Kirkuk (B), and the North Gas Company outside the city of Kirkuk (C), where samples were collected at regular monthly intervals for a period of six months, from September 2022 until February 2025 the study focused on a set of measurements that included alkalinity in terms of calcium carbonate, ammonia, with an estimate of the amount of nutrients (nitrite, nitrate, and phosphate), as well as potassium ions, aluminum, and some of biological pollution, including BOD and COD, as well as E.coli bacteria, total coliform bacteria, yeasts and molds, as they were all exceeding the standard specifications, except for ammonia and nitrite,which were within the limits, as they showed a variation in medium basicity between the three companies, as the highest value was (467.01) for Company (A), and the lowest value was (25.03), with slight differences. As for nitrate, the results were between (3.9-50.9) mg/L. The average phosphate values exceeded the permissible limits of the Iraqi standards (3.0 mg/L), as they ranged between (1.7-7.9 mg/L), while the ammonia values ranged (0.07-79 mg/L) and the lowest rate for potassium was (2.1 mg/L) and the highest rate was (60.5 mg/L). As for aluminum, it ranged between (0.08-0.29 mg/L). The BOD5 values also showed a high concentration of organic matter in industrial waste water, which varied between (102.0-117.2 mg/L). The results of the study showed a difference in the numbers of E. coli bacteria between the months of the study, as the highest value was recorded during the month of September, which was 760,000 cells/100 ml.
Keywords: Chemical characteristics - microbiological characteristics - industrial water - oil companies.